Growth among Twins: Use of Singleton versus Twin-Specific Growth Nomograms - Mendez-Figueroa, Hector; Truong, Van Thi Thanh; Pedroza, Claudia; Chauhan, Suneet P. (American Journal of Perinatology, 2018)
Objective We hypothesized that utilization of a twin-specific nomograms, when compared with one based on singleton data, is less likely to classify twins as having abnormal growth and more likely to identify perinatal morbidity and mortality.Materials and Methods Data were culled from seven Maternal-Fetal Medicine Units (MFMU) studies, the included twin gestations in their study population. Each newborn twin's birth weight percentile was categorized using Alexander et al (singleton data) and Ananth et al (twin data) nomogram. Logistic regression models were adjusted for maternal race and body mass index, neonatal sex, study, and twin correlation.Results More twins were categorized as small for gestational age (SGA) when singleton nomogram was used (33%) compared with twin nomogram (4%). The use of singleton nomogram revealed a higher composite neonatal morbidity (CNM) and stillbirth rates among SGA twins but a similar neonatal mortality rate when compared with appropriate for gestational age. Correspondingly, when twin-specific nomogram was utilized, the CNM, odds of stillbirth, and neonatal mortality were higher among SGA twins. The rate of large for gestational age among twins was increased with the use of twin-specific nomograms.Conclusion Utilization of twin-specific nomogram is less likely to categorize twins as SGA and more likely to identify those at risk for stillbirth and neonatal mortality.
Keywords: twin; growth; nomogram